2019
DOI: 10.1155/2019/9408612
|View full text |Cite
|
Sign up to set email alerts
|

Altered Amplitude of Low-Frequency Fluctuations in Inactive Patients with Nonneuropsychiatric Systemic Lupus Erythematosus

Abstract: ObjectiveThis study is aimed at investigating the characteristics of the spontaneous brain activity in inactive patients with nonneuropsychiatric systemic lupus erythematosus (non-NPSLE). Methods Thirty-one female inactive patients with non-NPSLE and twenty healthy controls were examined by resting-state functional magnetic resonance imaging (RS-fMRI). Three amplitude methods including amplitude of low-frequency fluctuations (ALFF), fractional amplitude of low-frequency fluctuations (fALFF), and percent amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 68 publications
2
19
1
Order By: Relevance
“…Percent amplitude of fluctuation is a recently proposed amplitude metric with better test-retest reliability (Zhao et al, 2018;Jia et al, 2020). Studies have shown that PerAF is more sensitive than ALFF (Zhao et al, 2018;Yu et al, 2019;Jia et al, 2020); however, in contrast to the observed ALFF differences, we did not find significant PerAF alteration based on our present dataset. We speculate that this discrepancy might be associated with the distinct sample sizes and statistical methods of different studies.…”
Section: Figure 3 | (A)contrasting
confidence: 88%
See 1 more Smart Citation
“…Percent amplitude of fluctuation is a recently proposed amplitude metric with better test-retest reliability (Zhao et al, 2018;Jia et al, 2020). Studies have shown that PerAF is more sensitive than ALFF (Zhao et al, 2018;Yu et al, 2019;Jia et al, 2020); however, in contrast to the observed ALFF differences, we did not find significant PerAF alteration based on our present dataset. We speculate that this discrepancy might be associated with the distinct sample sizes and statistical methods of different studies.…”
Section: Figure 3 | (A)contrasting
confidence: 88%
“…Resting-state functional magnetic resonance imaging (rs-fMRI), a useful technique for exploring intrinsic neural activity via blood oxygen level-dependent signal (Biswal, 2012), has been increasingly utilized in detecting brain functional abnormalities and understanding the neural mechanism of various central nervous system disorders (Leon et al, 2014;Prodoehl et al, 2014;Koch et al, 2016;Takamura and Hanakawa, 2017;Gong et al, 2019;Ma et al, 2019). In recent years, several amplitude methods have been proposed to characterize the local properties of the rs-fMRI signal (Zang et al, 2007;Zou et al, 2008;Jia et al, 2020), and different metrics have shown their own specific characteristics (Zhao et al, 2018;Yu et al, 2019). Among these indices, ALFF provides direct characterization to the spontaneous brain activity at each voxel (Zang et al, 2007;Lv et al, 2019), and has been regarded as one of the most reliable and reproducible rs-fMRI parameters (Liu et al, 2016;Zhao et al, 2018;Zhi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PerAF is standardized at the single voxel level, the resulting spatial PerAF maps were then normalized with each voxel divided by the global mean PerAF (mPerAF). Both PerAF and mPerAF can be used for group-level statistical analysis, here we used mPerAF for further statistical analyses (Jia et al, 2019;Yu et al, 2019). For ReHo, the Kendall's coefficient of concordance (KCC) of the time course of every 27 nearest neighboring voxels was calculated (Zang et al, 2004).…”
Section: Static Alff Fractional Alff (Falff) Percent Amplitude Of Fmentioning
confidence: 99%
“…Our previous studies use the fALFF approach with different multiple correction and head motion correction but failed to find significant brain regions. 48 The middle frontal gyrus (MFG) was considered to be a site of convergence of the dorsal and ventral attention networks. 49 Previous studies found abnormalities in the middle frontal gyrus in SLE patients which were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers found increased standardized ALFF in the left inferior temporal gyrus and left putamen in patients with non-NPSLE and the significantly negative correlation between C3 and ALFF values in the left putamen was found in patients. 13 Liu et al 14 found abnormal ReHo in the parahippocampal gyrus, fusiform gyrus, and thalamus in non-NPSLE patients and ReHo values in the left postcentral gyrus were negatively correlated with anxiety depression symptoms. Yu et al 15 found decreased ALFF in the precuneus and increased ALFF in the right cuneus and right calcarine fissure surrounding cortex in non-NPSLE patients.…”
Section: Introductionmentioning
confidence: 99%